Intravenous levetiracetam in clinical practice – Results from an independent registry. (July 2015) - Lang, N.; Esser, W.; Evers, S.; Kellinghaus, C.; Nguento, A.; Schlegel, U.; Gaida, B.; Gburek-Augustat, J.; Altenmüller, D.M.; Burghaus, L.; Hoffmann, F.; Fiedler, B.; et al.
Abstract: Purpose: Most common clinical studies with antiepileptic drugs do not reflect medical everyday practice due to their strict in- and exclusion criteria and specifications of treatment regimens. Here we present a large non-interventional registry with the intention to evaluate the spectrum of applications in daily use and the efficacy and tolerability of intravenously given levetiracetam (LEV-iv). Methods: In a prospective approach of 17 neurological and neuropediatric centres in Germany LEV-iv treated patients of all ages were included over a period of 10 months. The observational period was 10 days with daily documentation of LEV-iv administration, type and frequency of seizures, currently used drugs and doses, and adverse events (AEs). In addition, treatment efficacy and tolerability were assessed by patients and physicians at study end as well as practicability of LEV-iv using a five-step scale. Results: In 95 patients LEV-iv was administered, 93 were included into the analysis. The median LEV-iv dose was 1500 mg (range 110–6000 mg) per day. Median age was 66 years (range 0.7–90.3 years). The majority of patients ( n  = 70, 75%) suffered from status epilepticus (SE, n  = 55, 59%) and acute seizure clusters ( n  = 15, 16%). Of those with SE, 41 patients (75%) had SE for the first time. Acute seizure clusters and SE terminated in 83% after LEV-iv administration. A total of 29 adverse events were reported in 17 of the 95 patients from the safety set. Ten of these were at least possibly related to LEV-iv treatment. Slight decrease of blood pressure during the infusion (3 patients each) was captured most frequently. No serious side effect was observed. Physicians rated the efficacy and tolerability of LEV-iv treatment as good or very good in 78% and 82% of the cases, respectively. Conclusion: In this large observational study of everyday practise the use of LEV-iv exhibited a remarkable good response and tolerability in patients with acute onset seizures (mostly SE). Further randomized controlled studies, like the established status epilepticus trial (ESET) are needed to confirm these findings.